2011
DOI: 10.1177/1073191110397274
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Version of the Cognitive Emotion Regulation Questionnaire

Abstract: The aim of this study was to validate a Spanish version of the Cognitive Emotion Regulation Questionnaire (CERQ-S), originally developed by Garnefski, Kraaij, and Spinhoven. To date, it is the only available instrument that permits a conceptually pure quantification of cognitive strategies of emotional regulation. A sample of 615 students (25% men; 75% women) completed the CERQ-S. Confirmatory factor analyses showed that, as in the original version, a nine-factor model also explained the data collected with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
118
1
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 28 publications
(49 reference statements)
16
118
1
15
Order By: Relevance
“…These results offer support for a lower use of adaptive strategies in psychopathology, contrasting with previous null results in the literature (Domínguez-Sánchez et al, 2013). Nevertheless, the findings also suggest that adaptive strategies are less relevant for psychopathology symptoms than maladaptive strategies.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…These results offer support for a lower use of adaptive strategies in psychopathology, contrasting with previous null results in the literature (Domínguez-Sánchez et al, 2013). Nevertheless, the findings also suggest that adaptive strategies are less relevant for psychopathology symptoms than maladaptive strategies.…”
Section: Discussioncontrasting
confidence: 57%
“…Past research has given adaptive strategies a less predominant role in psychopathology when compared with maladaptive strategies (Aldao & NolenHoeksema, 2010;Domínguez-Sánchez et al, 2013), while other studies have demonstrated the opposite (Kelly et al, 2012;Min et al, 2013). One main strong point of our research is that we compared differences in a wide range of symptoms while analyzing a diversity of adaptive and maladaptive strategies.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations